The Impact of the Uninhabitable House Assistance Program on the Welfare of Beneficiary Communities: A Study at BAZNAS Solok Regency - Dwi Azizah Putri; Rahmat Firdaus; Rizal; Febria Rahim (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Poverty and inadequate housing remain persistent issues in Solok Regency. As an effort to empower mustahik, the Solok Regency BAZNAS implements the Uninhabitable House Program (RTLH) through the construction and rehabilitation of homes for low-income communities. This study aims to describe the mechanism for determining program beneficiaries and to examine the program’s impact on their welfare. A descriptive qualitative approach was employed, using data collection techniques such as observation, interviews with commissioners, amil, and beneficiaries, as well as program documentation. The data were analyzed through the stages of reduction, presentation, and conclusion-drawing using source triangulation. The results show that beneficiary selection is carried out through application submission, administrative verification, field surveys, and deliberative decision-making. The RTLH program improves the physical feasibility of houses, enhances a sense of security, strengthens self-esteem, and promotes social interaction among beneficiaries, although challenges persist due to limited funding and restricted program coverage. Therefore, optimization in planning and expansion of program targets is needed going forward. These findings highlight the strategic role of zakat in poverty alleviation through the provision of decent housing at the regional level